Dermoscopy Evaluation of Erythema Dyschromicum Perstans Treated with Combination of Topical Steroid and Narrowband-Ultraviolet B: A Case Report - Triani, Aisha; Satya Wydya Yenny (HM Publisher, 2024)
Background: Erythema dyschromicum perstans (EDP), also known as ashy dermatosis, is an uncommon, acquired, and persistent skin condition identified by development of hyperpigmented macules of varying sizes on the trunk, face, and extremities. It exact cause is unknown, and there is ongoing debate surrounding its treatment. Dermoscopic assessments may prove beneficial in evaluating the effectiveness of therapeutic interventions. Case presentation: We present a case of a 20-year-old woman with numerous hyperpigmented macules of brown to slate-grey on her upper trunk, stomach, back, and extremities over the past three years. The patient reported no symptoms such as itching, numbness, or pain. Upon physical examination, mild anemia but otherwise healthy. On physical examination there are multiple brown-grey patches with reddish borders of varying sizes distributed across the body, with unaffected mucosa, scalp, palms, soles, and nails. Dermoscopic examination unveiled a widespread distribution of brown to grey backgrounds with a pinkish homogeneous appearance. Histopathological examination suitable for erythema dyschromicum perstans. The patient received a diagnosis of erythema dyschromicum perstans and underwent treatment involving a combination of topical steroids and Nb-UVB administered three times weekly for a duration of 8 weeks. Conclusion: This condition presents a cosmetic concern throughout the patient's lifetime and significantly affects their quality of life. After 8 weeks of the combination of topical steroids and Nb-UVB, there was a improvement of erythema and lesion appear lighter. This observation suggests that a treatment with a consistently favorable outcome has not been identified and necessitates further investigation.